A organização como um campo: o caso de uma fundação de apoio de uma instituição federal de educação profissional, científica e tecnológica - Lima, Luiz Otavio Gonçalves de (2019)
The emergence of the "third sector" in Brazil can be explained by the analysis of attempts to implement the economic development projects that occurred during the 20th century in the world, and especially in the Brazilian State. Among the organizations that integrate it are the foundations of support that currently constitute a reality of the operationalization of teaching, research and extension of the Federal Institutions of Professional, Scientific and Technological Education. However, the performance of these entities has received numerous criticisms, either by society or by the control bodies. Considering these questions at the national level and aware that the organizational study is permeated by theoretical approaches that fail to reveal the true dynamics of organizations, this research proposed the use of an alternative metaphor to the orthodox conceptualizations available for the understanding of institutions, suggesting that organization can be understood as a strategic field of action. Thus the present investigation had as objective to analyze the historical construction of the cultural- political dynamics of FADEMA, foundation of support of IFSULDEMINAS. In order to do so, a qualitative and longitudinal and retrospective research was performed, since the study does not refer to a certain moment, on the contrary, the research sought to explore facts that have occurred in the trajectory of FADEMA since its genesis until the year 2018. The research method used was the case study. As for data collection, this involved the bibliographical, documentary and semistructured interviews, which were analyzed and interpreted by the content analysis technique. In this way, it was observed that the metaphor used for this investigation allowed the understanding of the social construction of the FADEMA environment, as well as of its power relations, both determined by the internal and external dynamics of the field.